Women (re-)negotiating care across family generations: Intersections of gender and socioeconomic status - TIMONEN, VIRPI; CONLON, CATHERINE (My University, 2014)
Changing Generations, a study of intergenerational relations in Ireland undertaken between 2011 and 2013 by the Social Policy and Ageing Research Centre (SPARC), Trinity College, Dublin, and the Irish Centre for Social Gerontology (ICSG), NUI Galway, used the Constructivist Grounded Theory method to interrogate support and care provision between generations. This article draws on interviews with 52 women ages 18 to 102, allowing for simultaneous analysis of older and younger women’s perspectives. The intersectionality of gender and class emerged as central to the analysis. Socioeconomic positions shape contrasting forms of interdependency among family generations, ranging from “enmeshed” lives among lower socioeconomic groups to “freed” lives among higher socioeconomic groups. Women are initiating changes in how care and support flow across generations. Older women in higher socioeconomic groups are attuned to how emotional capital women expend across family generations can constrain (young) women’s lives. In an expression of solidarity, older women are renegotiating the place of care labor in their own lives and in the lives of younger women. A new reciprocity emerges that amounts to women “undoing gender.” This process is, however, deeply classed as it is women in higher socioeconomic groups whose resources best place them to renegotiate care.
PUBLISHED
Keywords: care; generation; socioeconomic status; reciprocity; Ageing; Inclusive Society